2013
DOI: 10.1158/1078-0432.ccr-13-0755
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Food and Drug Administration Approval: Carfilzomib for the Treatment of Multiple Myeloma

Abstract: The U.S. Food and Drug Administration (FDA) review leading to accelerated approval of carfilzomib is described. A single-arm trial enrolled 266 patients with multiple myeloma refractory to the most recent therapy who had received prior treatment with bortezomib and an immunomodulatory agent (IMID). Patients received carfilzomib by intravenous infusion over 2 to 10 minutes at a dose of 20 mg/m 2 on days 1, 2, 8, 9, 15, and 16 of the 28 days of cycle 1, and at a dose of 27 mg/m 2 on the same schedule in cycle 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
160
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(164 citation statements)
references
References 17 publications
0
160
0
2
Order By: Relevance
“…11,28 Carfilzomib-based regimens have been generally well tolerated, but concerns for CV toxicity have been raised. 10,[13][14][15]29 Here, we assessed carfilzomib-associated CV AEs in phase 1-3 clinical trials. Across all RRMM phase 3 trials, treatment with carfilzomib was associated with a numeric increase in cardiac AE incidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,28 Carfilzomib-based regimens have been generally well tolerated, but concerns for CV toxicity have been raised. 10,[13][14][15]29 Here, we assessed carfilzomib-associated CV AEs in phase 1-3 clinical trials. Across all RRMM phase 3 trials, treatment with carfilzomib was associated with a numeric increase in cardiac AE incidence.…”
Section: Discussionmentioning
confidence: 99%
“…12 In pivotal phase 2 and 3 studies, there has been a reported increase in CV AEs. 10,[13][14][15] In the phase 3 ASPIRE and ENDEAVOR studies, the grade $3 cardiac failure incidence was 3.8% (KRd) vs 1.8% (Rd) and 4.8% (Kd) vs 1.8% (Vd). 10,15 Post hoc analyses of ASPIRE and ENDEAVOR data according to age showed increased cardiac failure risk in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although proteasome inhibitor treatment of cells may not represent a physiologic condition, it is important to understand the therapeutic effects of proteasome inhibitors as bortezomib (Velcade) and carfilzomib (Kyprolis) are approved drugs for the treatment of multiple myeloma (64,65). The reduction of 26S proteasome function is a physiologically relevant situation.…”
Section: Discussionmentioning
confidence: 99%
“…12,51 However, there is a pressing need to understand mechanisms of resistance to proteasome inhibitors such as bortezomib and to develop strategies active against such resistant cells. Previous efforts have highlighted the contribution of the antiapoptotic Bcl-2 family protein Mcl-1 to MM cell survival and bortezomib resistance, 52 but recent attention has focused on the role of proapoptotic BH3-only proteins (eg, Bim) in MM responsiveness to bortezomib.…”
Section: Discussionmentioning
confidence: 99%